Degrowth Analysis on Indonesian International Tourism Destinations - Nuryananda, Praja Firdaus; Rudiany, Novita Putri; Najaf, Abdul Rezha Efrat; Mawardi, Alfiandi Imam; Hamdan, Arva Rizqullah; Bilqis, Thufailah Nafiisah; Zein, Isynariyah (Universitas Airlangga, 2024)
Greenwashing has become prevalent as many stakeholders falsely claim to adhere to green growth principles. Green growth also often neglects human rights aspects. This study proposes degrowth as an alternative to the dominant economic growth paradigm. Degrowth, which gained popularity during the post-pandemic recovery, emphasizes sustainability, justice, and independence from capitalist growth. While green growth often relies on technology for solutions, degrowth recognizes its potential limitations. In the Global South, degrowth can support local communities and challenge neo-colonial tourism practices. Community-based tourism, slow tourism, and responsible tourism are concrete manifestations of degrowth principles. These approaches aim to benefit local communities, reduce environmental impact, and promote sustainable tourism practices. This study focuses on three Indonesian international tourism destinations, Raja Ampat, Nusa Penida, and Labuan Bajo. By analysing the discourses surrounding these destinations, the study highlights the need for a transformative shift towards more sustainable and equitable tourism practices. Degrowth offers a roadmap for achieving balanced economic growth while prioritizing ecological preservation and social justice. Keywords: Green Growth, Degrowth, Sustainability, Justice, Tourism.